Educación superior en clave digital: Una apuesta de la Universidad Santo Tomás para articular sus funciones sustantivas y fortalecer la formación integral (2020)
The following article presents the normative, epistemological and techno-pedagogical foundation of the educational innovation process implemented by the Department of Humanities of the Santo Tomás University (Bucaramanga Section) that is aimed at improving and redefining the teaching-learning process from a virtual perspective, With which it is tried to strengthen the integral formation, to humanize the digital scenes and to promote the development of the investigative abilities like articulating axis of the knowledge to offer a personal learning environment that favors the students of the Institution.